Advanced materials for structural components of Indian sodium-cooled fast reactors. (March 2016) - Bhaduri, A.K.; Laha, K.; Ganesan, V.; Sakthivel, T.; Nandagopal, M.; Reddy, G.V. Prasad; Kumar, J. Ganesh; Vijayanand, V.D.; Selvi, S. Panneer; Srinivasan, G.; Das, C.R.; Nagesha, A.; et al.
Abstract: The performance of fast reactor (FR) working under high temperature, moderate pressure and intense neutron irradiation depends on its structural materials. Type 316 LN austenitic stainless steel with 0.02–0.03 wt.% carbon and 0.06–0.08 wt.% nitrogen is generally used for structural components of FR along with modified 9Cr–1Mo ferritic steel for steam generator. With an aim of enhancing the life of FR, efforts towards the enhancement of strength of the materials are been described. Nitrogen content in the 316 LN steel has been increased for optimizing the tensile, creep, fatigue and creep–fatigue interaction strengths. Both the tensile and creep strength were found to increase with nitrogen content; whereas the fatigue and creep–fatigue interaction strength have optimum values at around 0.12 wt.% of nitrogen. Based on the study, nitrogen content in 316 LN steel has been optimized at 0.11–0.13 wt.% for optimum combination of strengths. Weldability study has been performed and matching welding consumable has been developed. Creep strength enhancement of modified 9Cr–1Mo steel and its fusion welded joint has been addressed through microalloying the steel with boron along with the restriction on nitrogen content. The microalloying not only improves the creep strength of the steel also reduces the type IV cracking susceptibility of the fusion welded joint of the steel. The optimum contents of boron and nitrogen in the steel have been identified as around 60 ppm boron and 100 ppm nitrogen for better creep strength and type IV cracking resistance. The paper describes the challenges in developing the materials.